ANALISIS KEBIJAKAN DALAM KONTEKS SOSIAL, POLITIK, DAN EKONOMI: KETERKAITAN KEBIJAKAN PENDIDIKAN DENGAN DINAMIKA EKSTERNAL - Dewi Tsalitsul Hamidah; Eka Herianto; Kholid Abdul Hafiedz; Masduki Duryat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education policy is a crucial instrument in improving the quality of human resources and supporting national development. However, education policy cannot be separated from the influence of various external factors, including social, political, and economic contexts. This study aims to analyze education policy within these contexts and examine its relationship with evolving external dynamics. The method used is a descriptive qualitative approach with literature study as the primary data source. The results indicate that social factors influence education policy through societal values, culture, and educational needs. Political factors play a role in determining policy direction based on the ideology, interests, and programs of the ruling government. Meanwhile, economic factors are closely related to a country's ability to provide funding, infrastructure, and teacher welfare. In addition, external dynamics such as globalization, technological advancement, and changes in labor market demands require education policies to be adaptive and responsive. Therefore, comprehensive policy analysis is essential to ensure that education policies are relevant, effective, and capable of addressing contemporary challenges.